THE STUDENTS’ MATHEMATICAL CREATIVE THINKING ABILITY OF JUNIOR HIGH SCHOOL THROUGH PROBLEM-SOLVING APPROACH - Heris Hendriana; Fika Muji Fadhillah (IKIP Siliwangi and I-MES, 2019)
This study aims to examine the achievement and improvement of mathematical creative thinking skills of students whose learning uses a problem-solving approach compared to those using ordinary learning and the implementation of learning steps using a problem-solving approach in the field. The method used in this study is a quasi-experimental method, because there is manipulation of treatment, where the experimental class uses learning with a problem-solving approach, and the control class uses ordinary learning. The population in this study were all seventh-grade students of SMP Negeri 1 Cilamaya Wetan. With the subject of the sample are two classes VII, while the sample was chosen 2 classes randomly where the experimental class obtained learning with a problem-solving approach, and the control class gained regular learning. Class VII L as the experimental class and class VII I as the control class. The instrument in this study is a set of test questions in the form of a description consisting of eight questions. Based on the results of research and analysis of pretest, posttest, and n-gain data, it was found that the achievement and improvement of students' creative mathematical thinking skills using problem-solving approaches compared to those using ordinary learning, and implementation of learning steps with problem-solving approaches in the field showed that the learning process is more effective and creative in mathematical problems solving.